Structures of three disubstituted [13]-macrodilactones reveal effects of substitution on macrocycle conformation - Rutledge, Kelli M. (Acta Crystallogr E Crystallogr Commun, 2020)
The synthesis and crystal structures of three new disubstituted [13]-macrodilactones, namely, trans-4,8-dimethyl-1,10-dioxacyclotridec-5-ene-2,9-dione, C(13)H(20)O(4), I, cis-4-(4-bromophenyl)-13-methyl-1,10-dioxacyclotridec-5-ene-2,9-dione C(18)H(21)BrO(4), II, and trans-11-methyl-4-phenyl-1,10-dioxacyclotridec-5-ene-2,9-dione, C(18)H(22)O(4), III, are reported and their conformations are put in the context of other [13]-macrodilactone structures reported previously. Together, they show that the number, location, and relative disposition of groups attached at the termini of planar units of the [13]-macrodilactones subtly influence their aspect ratios.